2015
DOI: 10.1186/s13287-015-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of human mesenchymal stem cells helps to reduce adiposity and improve glucose tolerance in an obese diabetic mouse model

Abstract: IntroductionHuman mesenchymal stem cells (MSCs) are multipotent cells that can differentiate into fat, muscle, bone and cartilage cells. Exposure of subcutaneous abdominal adipose tissue derived AD-MSCs to high glucose (HG) leads to superoxide accumulation and up-regulation of inflammatory molecules. Our aim was to inquire how HG exposure affects MSCs differentiation and whether the mechanism is reversible.MethodsWe exposed human adipose tissue derived MSCs to HG (25 mM) and compared it to normal glucose (NG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Our results corroborate well with the findings from various insulin‐resistant tissues or cell types, including human samples. HG‐treated human mesenchymal stem cells from adipose tissue exhibited a decreased OCR in a time‐dependent manner (71). Insulin‐resistant cerebral arteries from obese rats exhibited impairments in mitochondrial functions, coupled with a decrease in mitochondrial proteins (72).…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate well with the findings from various insulin‐resistant tissues or cell types, including human samples. HG‐treated human mesenchymal stem cells from adipose tissue exhibited a decreased OCR in a time‐dependent manner (71). Insulin‐resistant cerebral arteries from obese rats exhibited impairments in mitochondrial functions, coupled with a decrease in mitochondrial proteins (72).…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy, particularly in the form of MSCs, has emerged as a novel technique in suppressing the immune response after transplantation, owing to MSCs causing fewer side effects compared with immunosuppressants. While MSCs have been used in multifarious organ transplants [3941] including SBTx [24, 42], there has been an increased focus on overcoming transplantation limitations and enhancing MSC function [4347]. This study was designed to investigate whether the cytoprotective and immunosuppressive protein, HO-1, could improve the survival rate of BMMSCs in vivo and reinforce SBTx protection.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies have shown that high glucose stimulates proliferation and enhances osteogenic differentiation potential in mesenchymal stem cells (MSCs) [6]. These diverse responses to the high glucose condition may be relevant for the different glucose tolerance of stem cells [7, 8]. Therefore, further investigation into the underlying mechanism of high glucose on stem cell functions is needed to develop a therapeutic strategy for stem cell therapy.…”
Section: Introductionmentioning
confidence: 99%